The scarring effects of unemployment, low pay and skills under-utilisation in Australia compared - Sloane, P; Mavromaras, K; Sloane, Peter; Mavromaras, Kostas; Zhang, Wei (My University, 2015)
There is a substantial literature on the scarring effects of unemployment on future employment prospects and a smaller one on the scarring effects of low pay, but the possibility that skills mismatch, in the form of skills under-utilization, may have similar detrimental effects has not been considered before. We use the Household, Income and Labour Dynamics in Australia panel to investigate the dynamics of unemployment, low pay and skills under-utilization, including differences by gender and education. We show that, in addition to earlier evidence on wage penalties and reduced job satisfaction, skills under-utilization scars future employment prospects in a way similar to that of low pay
Keywords: Employment -- Unemployment; Employment -- Deskilling; Education and Training -- Workplace; Learning, education and training; Labour market; Employment; Education and Training; Unemployment; Deskilling; Workplace; Learning, education and training; Employment and unemployment